New Megathrust Locking Model for the Southern Kurile Subduction Zone Incorporating Viscoelastic Relaxation and Non‐Uniform Compliance of Upper Plate. Issue 5 (18th May 2021) - Itoh, Yuji; Nishimura, Takuya; Wang, Kelin; He, Jiangheng
Abstract: Dense Global Navigation Satellite System (GNSS) observations enable the development of megathrust interseismic locking models for the southern Kurile subduction zone where many great earthquakes have occurred. Inversion of these data assuming uniform elastic Earth has yielded slip deficit rates that are unreasonably high and/or full locking depth that is unreasonably large. Using the finite element method, here we construct a new Kurile locking model that includes interseismic viscoelastic stress relaxation and non‐uniform compliance of the elastic upper plate. Inverting the same geodetic data using the new subduction zone model alleviates the previously seen unreasonable features in inferred megathrust locking state. In the new model, full locking extends to shallower depths than the downdip limit of some large megathrust earthquakes including the 2003 M w 8.0 Tokachi‐oki earthquake, supporting the notion of the shrinking of the locked area before the earthquakes and/or propagation of seismic rupture into creeping areas as previously predicted by friction or dynamic rupture models. By modeling the effects of a few recent M 8 earthquakes, we show that postseismic transients of recent earthquakes, although second‐order, should be addressed in deriving megathrust locking models. The locking state near the trench cannot be resolved by the land‐based GNSS data regardless of the improved model rheology and structure, although independent observations, such as slow earthquakes, may be used to speculate on the near‐trench locking state in various part of the margin in the absence of seafloor geodetic observations. Key Points: Viscoelastic mantle relaxation and non‐uniform compliance of upper plate are of first order importance to interseismic deformation Invoking relaxation and non‐uniform compliance in geodetic inversion leads to shallower megathrust locking than in previous models Improved model structure and rheology do not improve resolution of near‐trench locking state, demonstrating need for seafloor geodesy